Analisis dan Perancangan Sistem Informasi Pembelajaran Berbasis Web di Smu 82 Jakarta - Luhukay, Devyano (Bina Nusantara University, 2010)
The purpose of this study was to analyze the constraints and the distribution system of learning information, and designing a web-based application that can be accessed 24 hours and support the dissemination of information relating to school and improving the quality of their students. The research method used was a field survey, literature, and interviews. UML design methodology covers the development, creation of database design and screen design. The results achieved are a school administration application that is used for learning information. The application also provides information on school officials. With this application, can facilitate the teachers and administration in making the charging and management of the information in high school. The conclusion was that with this application, the efficiency and effectiveness of time increases, the error value calculation is minimized. In addition, with this application, it also can improve the performance of teachers and administration. However, it is expected for the future, these applications can be developed better.